Contribution of air flow to impact attenuation in chamber structures - Lamb, Leslie R (University of Ottawa (Canada), 2008)
Head injuries are a major cause of morbidity and mortality worldwide, many resulting from sporting activities. Currently, there is a need in the head protection industry for improved technology capable of reducing the risk of mild and severe head injuries. Contemporary head protection devices are comprised mainly of foam and have several inherent disadvantages, including a limited ability to provide effective energy absorption under both low and high impact velocities. New thin-walled collapsible chamber energy absorption systems may resolve this problem. The chambers consist of four engineering elements which alter their performance - geometry, air volume, material, and venting system. This research analyzed the contribution of air flow through an orifice to the chamber's management of impact energy. The main objective of the study was to determine the effect of the chamber's vent diameter on peak force and venting rate during an impact. Two material stiffnesses and five vent diameters were tested at three inbound velocities. Each chamber was impacted ten times using a monorail drop system. Significant main effects were found for material stiffness, vent diameter, and inbound velocity on peak force and venting rate (p<0.0001). Under low inbound velocities the largest vent diameters transmitted less force than the smallest, while this relationship reversed at high inbound velocities. Under low velocities air flow rate was negatively, and flow duration was positively correlated to peak force. Under high velocities, air flow rate was positively, and duration was negatively correlated to peak force. This suggested that under low velocities chambers performed optimally when air was dissipated fast, for a short duration; however, as the chamber approached a critical failure region, the increased duration and decreased velocity of air released prevented larger peak forces. Overall, this research confirmed that engineered thin-walled collapsible chambers use air as a mechanism to absorb impacting force.
Keywords: Health Sciences, Recreation.; Biology, Physiology.